The corrosion behaviour of stainless steels and Ni-based alloys in nitrate salts under thermal cycling conditions in concentrated solar power plants. (15th January 2022) - Liu, Qingyang; Barker, Richard; Wang, Chun; Qian, Jiong; Neville, Anne; Pessu, Frederick
Highlight: Intermittent cooling effect during thermal cycling significantly influences the corrosion behaviour of alloys in Ar. Thermal cycles in Ar was observed to reduce CR compared to isothermal conditions. Ni-based alloys show better corrosion resistance than SSs at any conditions. Abstract: Molten nitrate salts are widely used as heat transfer fluids and heat storage media for concentrated solar power (CSP) plants due to their favourable thermo-physical properties. The corrosion of alloys in nitrate salts used in CSP plants poses a critical challenge to the safety, cost and efficiency of their operations under high temperature. In this study, the corrosion behaviour of stainless steels; 321 and 347, and Ni-based alloy; IN 625 and In 825, in Solar (nitrate) salts has been experimentally investigated under isothermal (at 600 °C) and thermal cycling (between 600 °C and 250 °C) conditions, and under argon atmosphere. Corrosion assessment of test materials was achieved using gravimetric measurements in a simulated metal – molten salt environment in a furnace for 7 days. The micro-morphology and cross-sectional analysis of the corroding interface was carried out using a combination of scanning electron microscopy, energy dispersive X-ray spectroscopy and X-Ray diffraction techniques. Compared with isothermal condition, thermal cycling between the 250 °C (for 12 hrs) and 600 °C (for 12 hrs) reduces the corrosion rate of test materials, the severity of corrosion attack and the thickness of corrosion product layers. The result also shows that corrosion product breakdown due to spallation was also reduced by lower time at maximum temperature and cooling effect during thermal cycling, especially in stainless steels when compared with isothermal conditions at 600 °C. The spallation process became prominent with the formation of a Na-Fe oxide layer at the corrosion interface. Ni-based alloys show better corrosion resistance than stainless steels under both isothermal and thermal cycling conditions due to the superior passivation behaviour from combined Cr and Ni enrichment. Cr2 O3 and NiO were formed as an inner layer in a multi-layered corrosion products on the metal surface from reaction with oxygen. Oxygen was made available from the decomposition of nitrate ions at 600 °C.